2005
DOI: 10.2307/4126475
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate Students' Experiences with an Arts-Based Unit: An Action Research

Abstract: I conducted an action research study with intermediate-level language and literature students, examining meaning making as adolescents engaged in a developmental writing and performance project. The study was guided by theory and research highlighting the valuable role of overt student reflection to improve engagement in learning. Data collection methods included interviews, teacher observations, reflective journals, and audio/videotaped performance. Data analysis was iterative throughout the study, using both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Researchers (Upitis & Smithrim ; Smithrim & Upitis ; Gamwell ) have found many benefits from the learning through the arts method: pupils became more engaged with science and other school activities and they enjoyed learning. Surveys of LTTA pupils, teachers, parents and administrators referred repeatedly to the ‘cognitive, physical, emotional, and social benefits of learning in and through the arts’ (Smithrim & Upitis , 120).…”
Section: Previous Studies About Learning Through the Artsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers (Upitis & Smithrim ; Smithrim & Upitis ; Gamwell ) have found many benefits from the learning through the arts method: pupils became more engaged with science and other school activities and they enjoyed learning. Surveys of LTTA pupils, teachers, parents and administrators referred repeatedly to the ‘cognitive, physical, emotional, and social benefits of learning in and through the arts’ (Smithrim & Upitis , 120).…”
Section: Previous Studies About Learning Through the Artsmentioning
confidence: 99%
“…Surveys of LTTA pupils, teachers, parents and administrators referred repeatedly to the ‘cognitive, physical, emotional, and social benefits of learning in and through the arts’ (Smithrim & Upitis , 120). According to Gamwell (), learning through the arts has increased all learning modalities (aural, visual and kinaesthetic). When students are engaged physically and mentally in learning situations, they are more likely to retain the information.…”
Section: Previous Studies About Learning Through the Artsmentioning
confidence: 99%
“…Therefore, as the researcher in this study, I determined I would also serve in the dual role as an active participant. From his personal research experience, Gamwell (2005) reported the benefits as serving in the dual role of researcher and educator. "The intimate connection between me, as teacher and researcher, and the students provided an excellent opportunity to obtain the rich data from which to develop a thick description of the students' experiences" (p. 365).…”
Section: Participantsmentioning
confidence: 99%
“…Based on what participants proposed, presented, and learned, the unit of study's title demonstrates a shift from participants thinking about the local as narrowly defined by geo-political borders, to a more inclusive understanding of cross border regional influences. I shared in multiple roles of participant, observer, and researcher as we collected and analyzed data about place and people (Gamwell, 2005;Heron & Reason, 2007).…”
Section: First and Second Person Researchmentioning
confidence: 99%